Assessment On Flow Characteristics Of Dam Spillway Structure Using Physical Laboratory Model And Computational Fluid Dynamics - Che Ismail, Che Mohamad Amirus Shafiq (2017)
Spillway is a structure that release surplus water from a dam into downstream area. Without spillway, water will be overtopping the dam and collapse during heavy raining season. During releasing large flow discharge, higher water surface profile and high velocity flow occur. This situation have the tendency for the flow to overtopping and breaching out the spillway. High velocity cause low or negative pressure on the spillway slab, scouring and erosion at downstream area. Negative pressure leads to cavitation and may cause critical damage on spillway structure. This study aims to investigate the flow characteristics along spillway such as water depth, velocity, pressure and energy dissipation on the stilling basin. The study were attempt on the physical experiment and Computational Fluid Dynamic (CFD). A 1:20 scaled spillway physical model was constructed and assembled in Hydraulic Laboratory of Universiti Sains Malaysia. This study has been conducted on four different flow rate (0.012 m3/s, 0.017 m3/s, 0.021 m3/s and 0.067 m3/s) with total of 62 measurement points for each case. The data were measured and recorded on the selected points. To ensure the release flow is safe from causing severe damage on the downstream area, the study then was focused on stilling basin. For CFD, ANSYS FluentTM used as the solver for this study. After obtaining the required results from CFD, the values were compared to the physical model data for validation. Based on the original design, hydraulic jump length and depth were overtopping the side bank wall of the model for all flow discharge. Three modifications on the stilling basin were suggested to reduce the depth and length of hydraulic jump. The velocity reduced from these four tested stilling basin ranging from 54% to 64%. The length and depth of the hydraulic jump reduce as suggested on the 2nd modification. As for energy dissipation, original configuration yield the most value averagely compare to the others. By validating the results for both method, a good agreement was achieved for the water surface profile, velocity and pressure. The scatter plot relationship between physical experiment and numerical analysis having the regression coefficient (R2) ranging from 0.97 to 0.99. End results shows that the velocity, length and depth of hydraulic jump at the end of spillway can be reduce more by having a bigger dimension with additional row of buffer blocks while having the same length of stilling basin. Thus, it can be concluded that CFD can be used to simulate the flow characteristics in spillway as an alternative to physical experiment of spillway.